Mitochondrial injury induced by triclopyr in the rat liver - Rizzi, J. S. [UNESP]; Seloto, D. G. [UNESP]; Pereira, L. C. [UNESP] (Taylor & Francis, 2025)
The herbicide triclopyr (3,5,6-trichloro-2-pyridinyloxyacetic acid) is already considered an environmental problem due to damage caused by incorrect disposal, leaching, and aerial dispersion, which may pose risks to the environment and human health. Studies have evaluated metabolism, absorption, excretion, and active transport but there is no clear information about its mode of action (MoA) and its cytotoxic action potential remains unknown. In this context, mitochondria have been used to assess the toxicity of xenobiotics, for this reason, to identify the toxic mechanism of triclopyr, hepatic mitochondria from Wistar rats were exposed in vitro to different concentrations of triclopyr (0.5–500 µM). There was neither formation/accumulation of reactive oxygen and nitrogen species, nor lipid peroxidation or changes in the mitochondrial antioxidant system, in addition to proper functioning of oxidative phosphorylation and ATP production. Changes were found in NAD(P)H oxidation, membrane potential dissipation and mitochondrial calcium gradient. These results demonstrate that mitochondria suffer damage related to their bioenergetics and redox status but not to their structure when exposed to concentrations of triclopyr considered higher than those described as found in the environment so far.Highlights Triclopyr has a low mitochondrial uncoupling potential. The damage caused to the bioenergetics and redox state of the mitochondria is related to concentrations considered higher than those found in the environment. Even at high concentrations, triclopyr was not able to change the structure of the organelle after exposure. Oxidative phosphorylation and ATP production were not impaired after exposure. NAD(P)H oxidation resulted in potential membrane dissipation and mitochondrial calcium gradient dissipation. Triclopyr does not have RONS-forming properties, as well as it does not peroxide membrane lipids, it preserves membrane sulfhydryl groups and maintains the normality of the GSH/GSSG ratio.
Keywords: emerging contaminants; herbicide; Mitochondrial damage; pesticides; toxicity; triclopyr; xenobiotics